Trader vic on commodities : - Sperandeo, Victor (John Wiley & Sons, 2008)
In Trader Vic on Commodities, Wall Street legend Victor Sperandeo explains in simple terms how these markets operate, removes some of the mystique and uncertainty involved, and offers a proven method for capitalizing on commodity market trends—without taking giant risks. Sperandeo shows that, as commodities are cyclical in nature, your goal should be to capture as much of the major market trends as possible, while balancing that goal with a minimum of risk.